2022
DOI: 10.3390/cancers14194550
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Testing for Mismatch Repair in Neoplasms Using Multiple Laboratory Methods

Abstract: Background: A deficiency in DNA mismatch repair function in neoplasms can be assessed by an immunohistochemical (IHC) analysis of the deficiency/loss of the mismatch repair proteins (dMMR) or by PCR-based methods to assess high microsatellite instability (MSI-H). In some cases, however, there is a discrepancy between the IHC and MSI analyses. Several studies have addressed the issue of discrepancy between IHC and MSI deficiency assessment, but there are limited studies that also incorporate genetic/epigenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
7
0
2
Order By: Relevance
“…The prevalence of dMMR in patients with CRC is higher in early stages than in advanced disease, and higher in western populations [ 25 , 26 ]. The prevalence in our study (6%) overlaps with that reported in two recent series in real-world practice in the US using the Veterans Affairs Health Care System [ 27 ] and the MD Anderson Cancer Center [ 28 ] databases. It is also within the range shown in a recent review that included a pooled analysis [ 26 ].…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of dMMR in patients with CRC is higher in early stages than in advanced disease, and higher in western populations [ 25 , 26 ]. The prevalence in our study (6%) overlaps with that reported in two recent series in real-world practice in the US using the Veterans Affairs Health Care System [ 27 ] and the MD Anderson Cancer Center [ 28 ] databases. It is also within the range shown in a recent review that included a pooled analysis [ 26 ].…”
Section: Discussionsupporting
confidence: 79%
“…The genomic tumor DNA was extracted and purified using AllPrep kit on a QIAcube liquid handling platform (Qiagen, Germantown, MD, USA) [ 23 ]. The peripheral blood DNA (a default source of germline DNA received in an EDTA tube) was extracted and purified using a Maxwell RSC Blood DNA Kit (Promega, Madison, WI, USA) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…2 and 4 ). To further rule out MLH1 involvement, additional BRAF (for CRC) and/or MLH1 promoter methylation analysis for other tumor entities should be considered if necessary [ 20 , 33 ]. Isolated loss of MSH6 has also been described for rectal cancer after chemoradiation [ 3 , 8 ], although this is typically not associated with MSI‑H.…”
Section: Unusual Dmmr Findingsmentioning
confidence: 99%
“…Supplementary molecular testing should be performed for further clarification of MMR-IHC findings that are ambiguous or unusual. MLH1 promoter methylation testing (or BRAF mutation testing for CRC; [ 33 ]) and NGS analysis of the tumor may be useful in clarifying the MMR gene mutation status. However, microsatellite analysis by NGS should be validated for each organ system against MMR-IHC and MSI-PCR as the reference method [ 10 , 11 , 28 ].…”
Section: Update On Step-by-step Assessment Of Mmr-ihcmentioning
confidence: 99%